2017
DOI: 10.3324/haematol.2016.158303
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of circulating plasma cells in patients with multiple myeloma: implications for plasma cell leukemia definition

Abstract: The presence of circulating plasma cells in patients with multiple myeloma is considered a marker for highly proliferative disease. In the study herein, the impact of circulating plasma cells assessed by cytology on survival of patients with multiple myeloma was analyzed. Wright-Giemsa stained peripheral blood smears of 482 patients with newly diagnosed myeloma or plasma cell leukemia were reviewed and patients were classified into 4 categories according to the percentage of circulating plasma cells: 0%, 1–4%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 32 publications
1
106
1
4
Order By: Relevance
“…The incidence of PCM patients with cPCs was around 15-20% by morphologic exam of Wright-Giemsa stained PB smear (17,18), and the incidence increased up to 80% with slide based IF (19). The incidence of PCM patients with cPCs was around 15-20% by morphologic exam of Wright-Giemsa stained PB smear (17,18), and the incidence increased up to 80% with slide based IF (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of PCM patients with cPCs was around 15-20% by morphologic exam of Wright-Giemsa stained PB smear (17,18), and the incidence increased up to 80% with slide based IF (19). The incidence of PCM patients with cPCs was around 15-20% by morphologic exam of Wright-Giemsa stained PB smear (17,18), and the incidence increased up to 80% with slide based IF (19).…”
Section: Discussionmentioning
confidence: 99%
“…PCs in PB have been detected by various methods and the negative prognostic implication of cPCs has been well established in patients with plasma cell disorders. The incidence of PCM patients with cPCs was around 15-20% by morphologic exam of Wright-Giemsa stained PB smear (17,18), and the incidence increased up to 80% with slide based IF (19). Following development of FC technology, research for cPCs has mainly progressed using this modality.…”
Section: Discussionmentioning
confidence: 99%
“…The current diagnostic definition of PCL is not prospectively studied and delays many from receiving early aggressive management strategies due to underdiagnosis. The presence of 5% circulating clonal plasma cells has been suggested to improve detection . This has been echoed by a recent Mayo Clinic study in December 2018 that showed those diagnosed between 1971 and 2016 with > = 5% circulating plasma cells (CPCs) had much poorer survival outcomes compared with those who did not have CPCs on diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 5% circulating clonal plasma cells has been suggested to improve detection. 40 This has been echoed by a recent Mayo Clinic study in December 2018 that showed those diagnosed between 1971 and 2016 with > = 5% circulating plasma cells (CPCs) had much poorer survival outcomes compared with those who did not have CPCs on diagnosis. 41 The successful treatment of this patient with VCD and daratumumab may prove an effective induction strategy for similar patients with an aggressive presentation, who are not candidates for AuSCT.…”
Section: Discussionmentioning
confidence: 99%
“…This approach should incorporate baseline risk evaluation and dynamic risk evaluation (MRD achievement and duration) during treatment (Figure 1). Baseline risk factors such as International Staging System (ISS), cytogenetics, lactate dehydrogenase (LDH) levels [117], extramedullary disease [118], circulating plasma cells [119], TP53 mutations [94], and many others can help define our therapeutic strategy. For instance, the use of double ASCT and long-term treatment with a PI plus IMiDs maintenance could be beneficial in the presence of high-risk cytogenetics [92].…”
Section: Future Perspectivesmentioning
confidence: 99%